A pharmacological examination of the cardiovascular effects of Malayan Krait (Bungarus candidus) venoms - Chaisakul, Janeyuth; Ahmad Rusmili, Muhamad Rusdi; Hodgson, Wayne C.; Hatthachote, Panadda; Suwan, Kijja; Inchan, Anjaree; Chanhome, Lawan; Othman, Iekhsan; Chootip, Krongkarn (MDPI, 2017)
Cardiovascular effects (e.g., tachycardia, hypo- and/or hypertension) are often clinical outcomes of snake envenoming. Malayan krait (Bungarus candidus) envenoming has been reported to cause cardiovascular effects that may be related to abnormalities in parasympathetic activity. However, the exact mechanism for this effect has yet to be determined. In the present study, we investigated the in vivo and in vitro cardiovascular effects of B. candidus venoms from Southern (BC-S) and Northeastern (BC-NE) Thailand. SDS-PAGE analysis of venoms showed some differences in the protein profile of the venoms. B. candidus venoms (50 µg/kg–100 µg/kg, i.v.) caused dose-dependent hypotension in anaesthetised rats. The highest dose caused sudden hypotension (phase I) followed by a return of mean arterial pressure to baseline levels and a decrease in heart rate with transient hypertension (phase II) prior to a small decrease in blood pressure (phase III). Prior administration of monovalent antivenom significantly attenuated the hypotension induced by venoms (100 µg/kg, i.v.). The sudden hypotensive effect of BC-NE venom was abolished by prior administration of hexamethonium (10 mg/kg, i.v.) or atropine (5 mg/kg, i.v.). BC-S and BC-NE venoms (0.1 µg/kg–100 µg/ml) induced concentration-dependent relaxation (EC50 = 8 ± 1 and 13 ± 3 µg/mL, respectively) in endothelium-intact aorta. The concentration–response curves were markedly shifted to the right by pre-incubation with L-NAME (0.2 mM), or removal of the endothelium, suggesting that endothelium-derived nitric oxide (NO) is likely to be responsible for venom-induced aortic relaxation. Our data indicate that the cardiovascular effects caused by B. candidus venoms may be due to a combination of vascular mediators (i.e., NO) and autonomic adaptation via nicotinic and muscarinic acetylcholine receptors